Cover Feature: Kinetic Enhancement of Direct Hydrogenation of MgB2 to Mg(BH4)2 upon Mechanical Milling with THF, MgH2, and/or Mg (ChemPhysChem 10/2019). Issue 10 (14th May 2019) - Sugai, Cody; Kim, Stephen; Severa, Godwin; White, James L.; Leick, Noemi; Martinez, Madison B.; Gennett, Thomas; Stavila, Vitalie; Jensen, Craig
Abstract : The Cover Feature illustrates how a modified form of magnesium boride that is highly activated toward hydrogenation can be used as a hydrogen storage material based on hydrogen cycling between Mg(BH4 )2 and MgB2 . The discovery of such a form of magnesium boride presents an important step towards the development of a practical onboard hydrogen storage system. More information can be found in the Communication by C. Sugai et al. on page 1301 in Issue 10, 2019 (DOI: 10.1002/cphc.201801187 ).